2015
DOI: 10.1111/1753-6405.12446
|View full text |Cite
|
Sign up to set email alerts
|

Cancers in Australia in 2010 attributable to tobacco smoke

Abstract: ObjectivesTo estimate the population attributable fraction (PAF) and numbers of cancers occurring in Australia in 2010 attributable to tobacco smoking, both personal and by a partner.MethodsWe used a modified Peto-Lopez approach to calculate the difference between the number of lung cancer cases observed and the number expected assuming the entire population developed lung cancer at the same rate as never smokers. For cancers other than lung, we applied the standard PAF formula using relative risks from a larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 15 publications
3
21
1
1
Order By: Relevance
“…Table summarises the PAF estimates for 26 cancer sites, and for all cancers collectively (excluding BCC and SCC of the skin), for each of the 13 factors appraised. Detailed reports including numbers of cases of cancer attributed to these factors and sensitivity analyses have been reported in companion articles 3–14 . In total, we found that 32% of all cancers (approximately 37,000 cases) diagnosed in Australia in 2010 (excluding BCC and SCC of the skin) could be attributed to the 13 factors (33% in men and 31% in women).…”
Section: Factors Declared As Modifiable Carcinogens: Reference Levelsmentioning
confidence: 76%
See 2 more Smart Citations
“…Table summarises the PAF estimates for 26 cancer sites, and for all cancers collectively (excluding BCC and SCC of the skin), for each of the 13 factors appraised. Detailed reports including numbers of cases of cancer attributed to these factors and sensitivity analyses have been reported in companion articles 3–14 . In total, we found that 32% of all cancers (approximately 37,000 cases) diagnosed in Australia in 2010 (excluding BCC and SCC of the skin) could be attributed to the 13 factors (33% in men and 31% in women).…”
Section: Factors Declared As Modifiable Carcinogens: Reference Levelsmentioning
confidence: 76%
“…Detailed reports including numbers of cases of cancer attributed to these factors and sensitivity analyses have been reported in companion articles. [3][4][5][6][7][8][9][10][11][12][13][14] In total, we found that 32% of all cancers (approximately 37,000 cases) diagnosed in Australia in 2010 (excluding BCC and SCC of the skin) could be attributed to the 13 factors (33% in men and 31% in women). Overall, tobacco smoke (PAF all cancers: 13.4%) was the leading Cancers in Australia in 2010 Summary and conclusion © 2015 The Authors cause of cancer in 2010, followed by solar radiation (6.2%), inadequate diet (6.1%) and overweight and obesity (3.4%), see Figure 1.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…For all causal factors considered in this project except infection, 8 smoking 9 and ultraviolet radiation (UVR), 10 this formula provides a suitable method for estimating the population attributable fraction. The calculation makes the following assumptions.…”
Section: Selection Of Risk Factorsmentioning
confidence: 99%
“…In the UK, it was estimated that, in total, 23% of the total cancer burden in men and 15% of the total burden of cancer in women was attributable to smoking [261]. In Australia an estimated 16% of all cancer cases in men and 10% of cancers in women (excluding BCC and cSCC of the skin) were attributable to tobacco smoking in 2010 [262].…”
Section: Smokingepidemiologymentioning
confidence: 99%